WAYS TO IMPROVE THE EFFICIENCY OF USING FIXED PRODUCTION ASSETS IN ENTERPRISES - Li Zhibo; Karimov Inomjon Ortikboyevich (Web of Journals Publishing, 2025)
This article examines the scientific and methodological aspects of improving the efficiency of using fixed production assets in construction enterprises. The role of fixed assets in the production process, their technical condition, and the key factors influencing economic efficiency are analyzed. In addition, practical ways to enhance fixed asset utilization efficiency are proposed based on fixed asset turnover, fixed asset profitability, and depreciation policy. The research findings contribute to increasing production efficiency in construction enterprises and improving managerial decision-making.
Keywords: Fixed production assets, efficiency, fixed asset turnover, fixed asset profitability, depreciation, construction enterprise.